DIFFERENCES IN AWARENESS OF DIABETES AMONG MALES AND FEMALES - Jayachandran, Sunaina; Pradeep, Shwetha; P., Tintu K.; Shajahan, Shehanaz; Mathew, Sheena; J., Sushmitha D.; Gowda, Tejaswini; Santhosh; Kundapur, Rashmi (Journal of Health and Allied Sciences NU, 2014)
Introduction: Metabolic diseases dramatically affect life of men and women from infancy up to old age and are a major challenge for clinicians. Sex and gender affect screening and diagnosis of metabolic diseases as well as treatment strategies and outcome.Aims & Objectives: To differentiate the knowledge of diabetes among both the gender and to study some practices like smoking, alcohol & exercise among males and females to avoid diabetesMaterials and Methods: Community based cross-sectional study. A questionnaire consisting of questions that were based on the knowledge, awareness and practices regarding the risk factors of Diabetes was prepared. Only students willing to participate in the study were included. The questionnaire was to be filled anonymously. We collected data from 600 adolescents of age group 16-18years out of which 364 were females and 236 were males.Results: According to our study the results showed that 82.63% males and 92% females think that had knowledge about diabetes, 61.8% males, 52.2% females had knowledge about the increase in rates of diabetics. 61.8% males and 52.2% females had knowledge about complications. 70.7%males and 73% females had knowledge about prevention of diabetes. 27.1% males and 24.4% females think there is complete cure for diabetes. Only 16.97%males and 11.8% females thought that they were at increased risk of diabetes.
Keywords: Diabetes; difference in sex; awareness; female awareness; knowledge of diabetes